2019
DOI: 10.3389/fpsyg.2019.02252
|View full text |Cite
|
Sign up to set email alerts
|

Digital Commensality: Eating and Drinking in the Company of Technology

Abstract: Commensality is a key aspect of social dining. However, previous research has identified a number of pros and cons associated with the incorporation of digital technology into eating and drinking episodes. For instance, those who are distracted by digital technology may eat/drink more (that is, they may overconsume) as a result of their failure to attend to the food-related sensations that are thought to cue the termination of eating. Similarly, it has often been suggested that the use of mobile devices at mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 132 publications
2
98
1
9
Order By: Relevance
“…Several studies have theorized that mukbang watching might have negative consequences for the viewers including (i) increased consumption of food because of social comparison or mimicry; (ii) alteration of viewers' perception of food consumption and thinness, eating, health, table manners, and eating manners because of modelling of bad behaviours; and (iii) obesity and different eating disorders because of glorifying binge eating (Bruno and Chung 2017;Donnar 2017;Hong and Park 2018;Park 2018;Shipman 2019;Spence et al 2019). On the other hand, mukbang watching might promote positive effects for viewers including alleviation of social isolation via creating a sense of belongingness to a community, subjective closeness for those who seek companionship and a dinner partner, and fulfilment of physical and sentimental hunger for those who are on a diet and/or live in single-person households (Donnar 2017;Hong and Park 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have theorized that mukbang watching might have negative consequences for the viewers including (i) increased consumption of food because of social comparison or mimicry; (ii) alteration of viewers' perception of food consumption and thinness, eating, health, table manners, and eating manners because of modelling of bad behaviours; and (iii) obesity and different eating disorders because of glorifying binge eating (Bruno and Chung 2017;Donnar 2017;Hong and Park 2018;Park 2018;Shipman 2019;Spence et al 2019). On the other hand, mukbang watching might promote positive effects for viewers including alleviation of social isolation via creating a sense of belongingness to a community, subjective closeness for those who seek companionship and a dinner partner, and fulfilment of physical and sentimental hunger for those who are on a diet and/or live in single-person households (Donnar 2017;Hong and Park 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In a review study about digital commensality (i.e. the practice of eating together), Spence et al (2019) argued how mukbang could be used to psychologically facilitate commensality in order to cope with eating alone. Their main concern was that there had been few empirical studies on how mukbang watching might affect viewers.…”
Section: Social Usementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have concluded that mukbang watching might have negative consequences for the viewers including (i) increased consumption of food because of social comparison or mimicry, (ii) alteration of viewers' perception of food consumption and thinness, eating, health, table manners, and eating manners because of modelling of bad behaviours, and (iii) obesity and different eating disorders because of the glorification of binge eating (Bruno and Chung 2017;Donnar 2017;Hong and Park 2018;Park 2018;Shipman 2019;Spence et al 2019). It has also been claimed that mukbang watching may also become addictive for a minority of people who use mukbang for social compensation (Malm 2014).…”
mentioning
confidence: 99%